2011
DOI: 10.3324/haematol.2011.042333
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of small lymphocytic lymphoma in the era of monoclonal B-cell lymphocytosis

Abstract: and Hasserjian RP. Reassessment of small lymphocytic lymphoma in the era of monoclonal B-cell lymphocytosis. Haematologica. 2011; 96:xxx doi:10.3324/haematol.2011.042333 Publisher's Disclaimer. E-publishing ahead of print is increasingly important for the rapid dissemination of science. Haematologica is, therefore, E-publishing PDF files of an early version of manuscripts that have completed a regular peer review and have been accepted for publication. E-publishing of this PDF file has been approved by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 37 publications
(80 reference statements)
1
61
0
1
Order By: Relevance
“…This is a crucial issue because previous studies 11 as well as more recent reports 15 showed that an under-recognized grey zone between SLL and cMBL may exist. This raises concerns about the fact that at least a portion of the cases classified as cMBL could represent SLL with a low and hidden nodal burden, and cast doubts on the appropriateness of a simple physical examination in the workup of cMBL patients.…”
mentioning
confidence: 94%
“…This is a crucial issue because previous studies 11 as well as more recent reports 15 showed that an under-recognized grey zone between SLL and cMBL may exist. This raises concerns about the fact that at least a portion of the cases classified as cMBL could represent SLL with a low and hidden nodal burden, and cast doubts on the appropriateness of a simple physical examination in the workup of cMBL patients.…”
mentioning
confidence: 94%
“…However, a recent study suggested that limited nodal involvement, usually discovered incidentally, was still compatible with a diagnosis of MBL. 30 Risk factors for progression included lymphadenopathy greater than 1.5 cm by imaging and the presence of proliferation centers on histology. Bone marrow biopsies in patients with MBL have shown patchy interstitial lymphoid infiltrates indistinguishable from low-level involvement by CLL and a diagnosis of CLL should not be made on this evidence alone without supporting clinical information.…”
Section: A B C Dmentioning
confidence: 99%
“…20 Recently, one study has proposed lymph node size to be a criterion for separating small lymphocytic lymphoma/chronic lymphocytic leukemia from monoclonal B lymphocytosis in lymph nodes, 21 but this is not applicable to the cases considered here. This observation confirms and expands previous descriptions of clonal B-cell population in the blood of HCV-infected persons, as well as clonal B-cell infiltrates in the bone marrow and liver biopsies of patients with HCV infection, associated or not with cryoglobulinemia.…”
Section: Discussionmentioning
confidence: 99%